Cognitive emotional regulation questionnaire-18 en universitarios: evidencias de validez convergente y discriminante - Dominguez-Lara, Sergio (2018)
Abstract The Cognitive Emotional Regulation Questionnaire (CERQ) was developed to assess cognitive emotional regulation strategies against unpleasant events. It was recently developed a short version (CERQ-18) in Peru and the results were favorable to assess their factorial equivalence regard to CERQ. The aim of this study was to analyze the relationship of CERQ-18 with external and internal criteria. In 286 college students aged 18 to 30 years old, was used a correlational analysis with measures of depression and anxiety. The results showed that the correlation pattern CERQ-18 and these measures was theoretically coherent, and also equivalent to the CERQ with these variables. The reliability of the dimensions of CERQ-18 was adequate, and estimate of the measurement error was similar to the long version. Finally, was conducted a statistical comparison between reliability coefficients of different short versions found. The implications of the results are discussed.